Context of Poetry Teaching - Bhandari, Indra Bahadur (Academia Research Journal, 2023)
Poetry is one of the most effective and widely written genres of literature. Looking at its form, it ranges from small compositions to large discourses. Poetry is created by the proper combination of sense and rhyme. It has a mixture of imagination and intelligence. The poem is written in both verse and prose styles. A specific form of language is used in poetry. Teaching the specific form of language poetry is considered as the most appropriate material to teach students of different levels the specific form of language. In poetry teaching, poetry teaching moves with the aim of improving pace, rhythm and rhythm, practicing reciting pronunciation, sentence structure, increasing vocabulary ability, developing compositional skills, develops the ability to express the meaning of specific characters, developing linguistic skills, and developing imagination. It is appropriate to do. Activities that attract students to the subject matter should be done first. After that, the difficulty related to semantics should be solved and knowledge on rhyming and poetic structure should be made. When teaching rhyming, first the teacher or the student should make ideal recitation, then group recitation and solo recitation should be done. After understanding the theme, the students should be encouraged to understand the poem after the question and answer session. As far as possible, pictures should also be displayed. The sense of intent should be made clear by repeatedly checking. An atmosphere should be created to determine the meaning of the poem itself. You should also make them write by giving questions that make the feeling clear. While doing these activities, students should be alerted if they leave the main part. Poetry is a very useful form of language teaching. Maybe the common reader has also enjoyed poetry, but learning linguistic skills is given priority while studying poetry.